Corneal Intrastromal Gatifloxacin Deposits following Uneventful Cataract Surgery - Suchismita Mishra; Lolly Pattnaik; Pradeep Kumar Panigrahi; Sakshi Ahuja (TNOA Journal of Ophthalmic Science and Research)
A 56-year-old male presented with progressive, painless vision loss in his left eye for the last four months. He was diagnosed with cataract (nuclear sclerosis grade four). He underwent uncomplicated phacoemulsification surgery for his left eye. Postoperatively, he was started on topical Gatifloxacin (0.3%) and prednisolone acetate (1%). Ten days following surgery, faint yellowish–white crystal-like deposits were noted in the anterior stroma in the inferior cornea. Gatifloxacin was promptly discontinued. Complete resolution of the deposits was noted three weeks following surgery. Corneal deposit of Gatifloxacin in the setting of intact epithelium is rare. Early diagnosis and prompt stoppage of the drug can result in complete resolution of the deposits.